How does E-Wallets Influence Consumptive Behaviour: The Role of Perceived Ease of Use and Security - Sonia Virgarini Nawi; Yonas Ferdinand Riwu; Dominikus K.T Aman (Komunitas Dosen Indonesia, 2025)
This study aims to examine the influence of perceived ease of use and security of e-wallets on the consumptive behavior of students in Kupang City. The analytical method employed is multiple linear regression, with 100 respondents collected through an online questionnaire distribution for analysis. The results indicate that the ease to use of e-wallets does not significantly effect of consumptive behavior, whereas e-wallet security has a significant influence. Simultaneously, both ease to use and security of e-wallets have an impact on consumer behavior. These findings contribute to theoretical development by strengthening the understanding of the importance of security in digital consumptive behavior among students, and also serve as a practical reference for e-wallet service providers should strengthen security features in order to build consumer trust. For example through digital education, transparency of privacy policies, and innovation in account protection features so that e-wallet adoption in this region becomes more widespread and sustainable.